Smart City - Future City? Smart City 2.0 as a Livable City and Future Market - Etezadzadeh, Chirine; SpringerLink (Online service) (Wiesbaden : Springer Fachmedien Wiesbaden : Imprint: Springer Vieweg, 2016)
The concept of a livable smart city presented in this book highlights the relevance of the functionality and integrated resilience of viable cities of the future. It critically examines the progressive digitalization that is taking place and identifies the revolutionized energy sector as the basis of urban life. The concept is based on people and their natural environment, resulting in a broader definition of sustainability and an expanded product theory. Smart City 2.0 offers its residents many opportunities and is an attractive future market for innovative products and services. However, it presents numerous challenges for stakeholders and product developers.
Challenges for Cities -- Product Development for Cities -- Social Change in Cities -- Digitalization of Urban Life -- Profile of Smart City 2.0.
Keywords: Energy policy; Energy and state; Environmental management; Transportation engineering; Traffic engineering; Energy Policy, Economics and Management; Environmental Management; Transportation Technology and Traffic Engineering